2013
DOI: 10.1007/s10531-013-0484-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific phenotypic variability of plant functional traits in contrasting mountain grasslands habitats

Abstract: 29 Empirical studies that link plants intraspecific variation to environmental conditions are 30 almost lacking, despite their relevance in understanding mechanisms of plant adaptation, in 31 predicting the outcome of environmental change and in conservation. Here, we investigate 32 intraspecific trait variation of four grassland species along with abiotic environmental 33 variation at high spatial resolution (n=30 samples per species trait and environmental factor 34 per site) in two contrasting grassland h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 61 publications
5
52
2
Order By: Relevance
“…Intra population trait variations are highly site and trait specific along the studied copper gradients and account for variable proportions of total variance (between 5 and 51%) depending on trait. This is consistent with results found along altitude or resource gradients (Wellstein et al, 2013;Lemke et al, 2015;Harzé et al, 2016;Pfennigwerth et al, 2017). Contrary to expectations, covariation with copper was less important compared to the site effect for most traits: only for size related traits was the impact of the local soil copper gradient superior to the site effect.…”
Section: Within Population Trait Variationsupporting
confidence: 91%
See 1 more Smart Citation
“…Intra population trait variations are highly site and trait specific along the studied copper gradients and account for variable proportions of total variance (between 5 and 51%) depending on trait. This is consistent with results found along altitude or resource gradients (Wellstein et al, 2013;Lemke et al, 2015;Harzé et al, 2016;Pfennigwerth et al, 2017). Contrary to expectations, covariation with copper was less important compared to the site effect for most traits: only for size related traits was the impact of the local soil copper gradient superior to the site effect.…”
Section: Within Population Trait Variationsupporting
confidence: 91%
“…Most studies focus on between population trait variation along altitudinal and latitudinal gradients (Souto et al, 2009;Fajardo and Piper, 2011) but studies comparing within species variation along several similar environmental gradients are scarce. However, growing evidence indicates that intra-population variation can be as large as inter-population variation along soil depth, light, temperature, nutrients or altitude gradients (Bresson et al, 2011;Wellstein et al, 2013;Lemke et al, 2015;Harzé et al, 2016;Pfennigwerth et al, 2017). This can result from two, mutually non exclusive mechanisms i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of Wellstein et al (2013) demonstrates that the intraspecific trait variation of four grassland plants along with abiotic environmental variation shows a significant phenotypic adaptation to diverging environmental conditions. A second review incorporating 28 studies (20 species, 224 traits, including genetic, vegetative and reproductive traits) showed that various grassland management regimes affect the selection pressure in plants differently (Pluess 2013).…”
Section: Effects On the Intraspecific Levelmentioning
confidence: 99%
“…First, differences in morphology, functional traits and resource acquisition strategies that are correlated with relative abundance are likely to produce sets of characteristics that are predictably associated with dominant and subordinate species, and these characteristics may be generalizable across a broad range of ecosystem types. However, it should be noted that, because plant traits, competitive abilities and niche differentiation are influenced by environmental factors (Koide, ; Wellstein et al ., ), a species can be simultaneously subordinate in a site and dominant in another depending on specific conditions. Second, recent evidence supports a much stronger functional role for subordinate species than Grime () originally envisioned, suggesting that relative abundance alone cannot be used to predict ecosystem function for all species groups.…”
Section: Reconciling Theories Of Subordinate Speciesmentioning
confidence: 99%